Descarte irregular de resíduos sólidos na área da subprefeitura da Sé: análise, perspectivas e o papel dos catadores - Queiroz, Marcos dos Santos (2023)
The generation of solid waste and garbage is inherent to the human being, whether in the city, in the countryside, on the beaches or forests. According to (AMLURB, 2017), the city of São Paulo, through the marked trade, pubs, restaurant, hotels and condominiums plus hospitals, produces around 18 thousand tons of solid waste every day. The residues accumulate in roads, squares and public places contributes to the degradation of the environment, bring health consequences, generate insecurity, testify against the image of the city, but on the other hand it is a source of income for cooperatives of collectors and recyclers. Starting from the following research question: “What makes people dispose of solid waste irregularly in the downtown center of São Paulo City?”. The objective of this work was to study, research and analyze the context of management, generation, and irregular solid waste disposal, in the section administrate by the municipality of Sé, São Paulo’s downtown. The methodology employed was based on bibliographical research, carried out in Scopus, Web of science, and TEDE – Digital Library of Theses and Dissertation of the Universidade Nove de Julho (UNINOVE), plus analysis of visits, interviews with the residents of the region, field visits and research legislation related to the subject. As results achieved, the importance of the region for the city was highlighted, abundant legislation on the subject was presented, the role of cooperatives was outlined, the contribution of recyclable collectors to the environment and a profile of the residents was utilized for the region in relation to the generation and destination of solid waste. It was concluded that the irregular disposal of solid waste needs to be faced rationally, from the perspective of education, prevention, and inspection, since the management of solid waste is necessary, as it is related to the protection and preservation of the environment. The limitation of this research was characterized by the absence of a survey of the biased points of irregular disposal of solid waste, but it opens a range for future research and deepening of the theme.